Analysis of Development and Forecasting of Cocoa Production on Community Plantations in West Sumatra: ANALISIS PERKEMBANGAN DAN PERAMALAN PRODUKSI KAKAO PERKEBUNAN RAKYAT DI SUMATERA BARAT - Sitanggang, Andreas; Candra, Delni Alek (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
Cocoa is one of the agricultural commodities that is the highest export commodity and has an important role in the movement of the national economy. National cocoa production is dominated by smallholder plantations and West Sumatra is one of the cocoa production centers in Indonesia which has a relatively high contribution to national cocoa production. Information on cocoa potential is needed to build the agricultural sector, especially in cocoa commodities. This study aims to analyze the development and predict the amount of cocoa production from smallholder plantations in West Sumatra Province. The research method used is quantitative descriptive using time series data from 2010-2024. The data used in this study are secondary data obtained from the Central Statistics Agency. The data analysis used to predict the amount of cocoa production from smallholder plantations is the Least Square method. The results of the study showed that throughout 2010-2024 cocoa production in West Sumatra tended to decline with an average decline of 1.59% and is projected to decline in 2025-2027 with an average decline of 2,304.08 tons per year.